Mechanical compression controls the biosynthesis of human osteoarthritic chondrocytes in vitro. (October 2020) - Chong, Pan Pan; Panjavarnam, Ponnurajah; Ahmad, Wan Nor Hanis Wan; Chan, Chee Ken; Abbas, Azlina A.; Merican, Azhar M.; Pingguan-Murphy, Belinda; Kamarul, Tunku
Abstract: Background: Cartilage damage, which can potentially lead to osteoarthritis, is a leading cause of morbidity in the elderly population. Chondrocytes are sensitive to mechanical stimuli and their matrix-protein synthesis may be altered when chondrocytes experience a variety of in vivo loadings. Therefore, a study was conducted to evaluate the biosynthesis of isolated osteoarthritic chondrocytes which subjected to compression with varying dynamic compressive strains and loading durations. Methods: The proximal tibia was resected as a single osteochondral unit during total knee replacement from patients ( N = 10). The osteoarthritic chondrocytes were isolated from the osteochondral units, and characterized using reverse transcriptase-polymerase chain reaction. The isolated osteoarthritic chondrocytes were cultured and embedded in agarose, and then subjected to 10% and 20% uniaxial dynamic compression up to 8-days using a bioreactor. The morphological features and changes in the osteoarthritic chondrocytes upon compression were evaluated using scanning electron microscopy. Safranin O was used to detect the presence of cartilage matrix proteoglycan expression while quantitative analysis was conducted by measuring type VI collagen using an immunohistochemistry and fluorescence intensity assay. Findings: Gene expression analysis indicated that the isolated osteoarthritic chondrocytes expressed chondrocyte-specific markers, including BGN, CD90 and HSPG-2 . Moreover, the compressed osteoarthritic chondrocytes showed a more intense and broader deposition of proteoglycan and type VI collagen than control. The expression of type VI collagen was directly proportional to the duration of compression in which 8-days compression was significantly higher than 4-days compression. The 20% compression showed significantly higher intensity compared to 10% compression in 4- and 8-days. Interpretation: The biosynthetic activity of human chondrocytes from osteoarthritic joints can be enhanced using selected compression regimes. Highlights: biosynthetic activity (proteoglycan) of osteoarthritic chondrocytes. chondrocytes were cultured using agarose scaffold and compressed dynamically. expression of collagen type VI (pericellular matrix) by osteoarthritic chondrocytes.